An Analysis of Coarse Aggregate Content of Hardened Concrete using Image Processing - Chuosavasdi , Thidaporn (Frontiers in Engineering Innovation Research, 2024)
The study aims to develop a method for the analysis of coarse aggregate content of hardened concrete using image processing. The developed method was applied to estimate the coarse aggregate content of hardened concrete prepared in the laboratory with a known mix design in order to verify its efficiency. The concrete samples were prepared in three different sizes with two types of cylindrical shapes and one type of cubic shape. Coarse aggregates with maximum sizes of ¾ inch and 1½ inches were used in the concrete mixture. The 0.40, 0.50, and 0.60 by weight water-to-cement ratios (w/c), and the 0.44 by volume of fine aggregate-to-aggregate ratio (s/a) were used for mixing. Subsequently, cross-sectional images of the concrete samples with each mix proportion and age were prepared to determine the coarse aggregate content. The analytical result of coarse aggregate content with maximum sizes of ¾ inch yields a lower margin of error than 1½ inches. The analytical results indicated that the maximum size of coarse aggregate significantly affects the analysis of the coarse aggregate content of hardened concrete with both cylinder-and cube-shaped of concrete samples. Additionally, the analysis demonstrates that increasing the water-to-cement ratio leads to higher variability in the results indicating that higher water content contributes to increased discrepancies. Moreover, both the age and the different cylindrical size of the concrete sample insignificantly affect analysis of the coarse aggregate concrete of hardened concrete.